An analysis of Mean Arterial Pressure, Roll Over Test and Body Mass Index as Predictors of Hypertension in Pregnancy - Hidayatun Nufus; Evi Rosita (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Hypertension in pregnancy is one of the three causes of maternal mortality in Indonesia,which proportion increases every year. More than 25% of maternal deaths in Indonesia in 2017 were causedby hypertension in pregnancy (Profil Kesehatan Indonesia, 2018).Purpose: The purpose of this study was to determine the relationship between MAP, ROT, and BMI onhypertension in pregnancy and to find predictor models of hypertension in pregnancy.Method: This research was conducted at Kedungadem Public Health Center, Bojonegoro Regency with across sectional study method. The sampling technique used purposive sampling with subjects consistingof 100 samples (50 normal tension and 50 hypertension). Data analysis used Chi Square, Logistic BinaryRegression and Area Under Curve.Results: The results showed that a history of preeclampsia (OR 10.29; 95% CI 2.21–47.9), MAP (OR 3.38;95% CI 2.36 4.84), ROT (OR 19.94; 95% CI5.47) -72.71), excess BMI (OR4.06; 95% CI 1.58-10.44), BMIof obesity (OR 4.8; 95% CI 1.26-18.24), were significantly associated with hypertension at 27 weeks of age.The main predictors of hypertension at 27 weeks were positive MAP (AUC 0.874; 95% CI 0.832-0.966; p =0.000) and for predictors at 32 weeks, positive ROT at 27 weeks, 28 weeks and 32 weeks (AUC 0.851; 95%CI 0.914-0.993; p = 0.000).Conclusion: The history of preeclampsia, MAP and BMI were able to predict at 27 weeks of gestation andROT was able to predict at 32 weeks of age.